Resistance Training and Glycogen Content in Ovariectomized Rats - Prestes, J.; Leite, R. D.; Pereira, G. B.; Shiguemoto, G. E.; Bernardes, C. F.; Asano, R. Y.; Sales, M. M.; Bartholomeu Neto, J.; Perez, S.E. A. (International Journal of Sports Medicine, 2012)
The aim of the present study was to investigate the effects of resistance training on glycogen content and muscle cross-sectional area (CSA) in ovariectomized rats. Wistar rats were divided into: sedentary; ovariectomized sedentary; resistance trained; and ovariectomized resistance trained. In the 12-week resistance training, the animals climbed a 1.1 m vertical ladder, 3 days per week, with 4–8 climbs. Cardiac, liver and muscle glycogen content was determined. After the 12-week resistance training period there was a higher hepatic and muscle glycogen content in the resistance training group compared with the other groups (p<0.01). CSA was higher in soleus for the resistance trained, ovariectomized resistance trained and sedentary compared with ovariectomized sedentary (p<0.05). Ovariectomy attenuated the increase in liver and muscle glycogen content, while soleus muscle cross-sectional area increased with resistance training, even in ovariectomized rats. Resistance training could be an important exercise to increase muscle function in situations of reduced estrogen and progesterone.
Keywords: resistance training; glycogen; skeletal muscle; ovariectomy; rats; cross-sectional area